Relationship of the 24-hour pattern of intraocular pressure with optic disc appearance in primary open angle glaucoma - Deokule, Sunil P. (2009)
PURPOSE: To study the relationship between the 24-hour pattern of intraocular pressure (IOP) with optic disc appearance in primary open angle glaucoma (POAG) patients. DESIGN: Observational clinical study. PARTICIPANTS: Seventy-five eyes of 45 POAG patients. METHODS: Patients underwent 24-hour IOP assessment in a sleep laboratory. Two observers classified the optic disc appearance for each eye into either concentric or non-concentric category. IOP measurements were taken in supine and sitting position during the diurnal period and in supine position during the nocturnal period. The mean, peak, trough and IOP range (peak – trough) were calculated for the office-hour period (9 AM to 4 PM), the diurnal period (7 AM-11PM), the nocturnal period (11 PM–7AM) and the 24-hour period. Further the difference in supine and sitting IOP during the diurnal periods were calculated and generalized estimating equations were used to compare IOP measurements in both groups. MAIN OUTCOME MEASURES: Diurnal and nocturnal IOP measurements. RESULTS: Forty eyes were classified as having concentric optic disc appearance and 35 eyes as having non-concentric optic disc appearance. The mean nocturnal IOP was significantly greater in the concentric group (24.0 ± 3.8 mm Hg; mean ± standard deviation [SD]) compared to the non-concentric group (21.9 ± 1.9 mm Hg; mean ± SD) (P = 0.004). The majority of IOP peaks of patients with the concentric optic disc appearance occurred during the nocturnal period as opposed to the diurnal period of patients with the non-concentric optic disc appearance. CONCLUSIONS: Concentric optic disc appearance may be associated with higher nocturnal IOP compared to non-concentric optic disc appearance.